DEVELOPMENT OF AUGMENTED REALITY-BASED MATHEMATICS LEARNING MEDIA TO FACILITATE STUDENTS’ MATHEMATICAL COMPUTATIONAL THINKING SKILLS: PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS AUGMENTED REALITY UNTUK MEMFASILITASI KEMAMPUAN BERPIKIR KOMPUTASI MATEMATIS PESERTA DIDIK - Majid, Ahmad Farham; Baharuddin; Nursalam; Tayeb, Thamrin; Andi Mattoliang, Lisnasari; Andi Kusumayanti; Amin, Badaruddin (MaPan : Jurnal Matematika dan Pembelajaran, 2024)
The development of digital technology has positively impacted the world of education, especially in creating more interactive and innovative learning media. The integration of Augmented Reality (AR) in learning is one of the innovations that can provide new learning experiences for students by presenting visualizations of abstract concepts in real life. This research aims to develop AR-based mathematics learning media to facilitate students’ mathematical computational thinking skills. The research method used is Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The research subjects involved 16 Insan Cendekia Sheikh Yusuf Gowa High School students. The research instruments used included product validation sheets, learner and teacher response questionnaires, and mathematical computational thinking ability tests. Analysis of research data focused on analyzing the validity, practicality, and effectiveness of Augmented Reality-based mathematics learning media. The results showed that the Augmented Reality-based mathematics learning media developed had met the criteria of validity, practicality, and effectiveness.